Hukum Harta Bersama Dalam Nikah Siri - Muhammad Amin Dali (At-Tanwir Law Review, 2021)
One of the polemics that remains interesting to study is unregistered marriage and its implications. Every marriage event should be recorded in front of the marriage registrar. Marriages that are not recorded are included in unregistered marriages, so they have quite large implications, one of which is the difficulty of dividing joint property in marriage. In this study, it will be discussed how the arrangement of joint assets of unregistered married couples after divorce according to Islamic families. The purpose of this study is to know the arrangement of joint property after divorce for unregistered married couples according to Islamic law, and to know the arrangement of joint property after divorce for unregistered married couples according to Islamic families. This research was conducted with a literature study approach, in which the data were analyzed by means of normative analysis. The results show that Islamic law does not regulate the distribution of joint property in marriage. However, from the point of view of the discovery of the law, joint property is included in 'urf which does not conflict with Islamic law. Shared assets also contain benefits and benefits for husband and wife. According to Islamic law which refers to the urf and maṣlaḥah mursalah methods, joint property must be divided after a divorce occurs, even if the divorce is from an unregistered marriage. The arrangement of the distribution follows customary law (urf) in one particular area. Joint assets of a married couple can be divided after a divorce occurs. However, the arrangement for the distribution of assets must go through the following procedures: First, married couples who are already divorced (divorced) must first apply for marriage isbat. Second, after the application is granted and a marriage certificate is obtained, the couple must apply for a divorce certificate through the Court. Third, after a divorce has been determined between the two, only then can the two spouses settle the joint property, and the distribution is equal. For unregistered married couples who are divorced due to death, there are no strict rules regarding the procedures and methods of dividing assets with unregistered married couples.